KOMPETENSI KERJA, KEPUASAN KERJA DAN MOTIVASI KERJA DALAM MEMPENGARUHI KOMITMEN ORGANISASI SERTA DAMPAKNYA BAGI KINERJA ASN PADA KANTOR KECAMATAN SITUBONDO - Suharyati, Bella Trisna; Ediyanto, Ediyanto; Tulhusnah, Lusiana (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The results of the hypothesis testing using the Smart PLS 3.0 application indicate that there is a significant direct influence of job competence on organizational commitment, job satisfaction on organizational commitment, work motivation on organizational commitment, job competence on Civil Servant performance, job satisfaction on Civil Servant performance, work motivation on Civil Servant performance, and organizational commitment on Civil Servant performance. However, the results of the hypothesis testing for indirect effects suggest that job competence does not significantly affect Civil Servant performance through organizational commitment, job satisfaction does not significantly impact Civil Servant performance through organizational commitment, and work motivation does not significantly influence Civil Servant performance through organizational commitment. On the other hand, the results of the hypothesis testing for indirect effects reveal that job competence does not have a significant influence on civil servant performance through organizational commitment, job satisfaction does not significantly affect civil servant performance through organizational commitment, and work motivation does not significantly impact civil servant performance through organizational commitment.